2020
DOI: 10.3389/fpsyg.2020.00018
|View full text |Cite
|
Sign up to set email alerts
|

Lactation and Work: Managers’ Support for Breastfeeding Enhance Vertical Trust and Organizational Identification

Abstract: Background: In working women, there are barriers when combining the mother and work role, especially during the breastfeeding period. Recent literature shows that improving organizational support increases trust performance via different domains (i.e., organizational identification) and that improving support for breastfeeding increases lactation rates and duration. Breastfeeding support in the workplace is one component that contributes to a mother's ability to continue to breastfeed once she has returned to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 29 publications
(38 reference statements)
2
10
0
Order By: Relevance
“…Employer support was also significant, especially in providing facilities for working mothers to express and store their breast milk [ 2 , 26 ]. Many studies have shown that the practice of breastfeeding declines once the mothers return to work [ 4 , 26 29 ]. In Malaysia there is no formal breastfeeding break allocated for mothers during working hours.…”
Section: Discussionmentioning
confidence: 99%
“…Employer support was also significant, especially in providing facilities for working mothers to express and store their breast milk [ 2 , 26 ]. Many studies have shown that the practice of breastfeeding declines once the mothers return to work [ 4 , 26 29 ]. In Malaysia there is no formal breastfeeding break allocated for mothers during working hours.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, in other studies involving other professional groups, the data indicated that coworker/supervisor support was not related to breastfeeding duration. 26,27 The question of whether the importance of breastfeeding support for healthcare professionals differs from other professions can be investigated in future comparative studies.…”
Section: Discussionmentioning
confidence: 99%
“…That is, data such as these can provide an empirical basis for determining a potentially desirable distance to the lactation room, which can be brought into a larger and more nuanced policy-level discussion (Hursh & Roma, 2013). In addition, beyond its salutary effects on breastfeeding, providing an easily accessible lactation room may be viewed by working mothers as contributing to a supportive breastfeeding environment which in itself may serve to increase breastfeeding (Gabriel et al, 2020;Hilliard, 2017;Spitzmueller et al, 2016Spitzmueller et al, , 2018, and is related to organizationally important outcomes including trust, organizational identity, affect, and work-family balance satisfaction (Gabriel et al, 2020;Lisbona et al, 2020).…”
Section: Policy and Workplace Implicationsmentioning
confidence: 99%